Synaptic and neuronal autoantibody-associated psychiatric syndromes (SNAps): Controversies and Hypotheses - Al-Diwani, Adam; Pollak, Thomas; Langford, Alex; Lennox, Belinda R. (Frontiers in Psychiatry, 2017)
Autoimmune Encephalitis (AE) mediated by antibodies against synaptic and neuronal surface targets frequently presents with a psychiatric syndrome. In these patients removal of autoantibodies treats the disease and outcomes are closely linked to early intervention. The discovery of these autoantibodies in isolated psychiatric syndromes has raised the possibility that these patients may derive similar benefits from immunotherapy, a potentially transformational approach to the treatment of mental illness. Although open-label case series suggest impressive therapeutic outcomes, the pathological relevance of these autoantibodies outside of canonical presentations is debated. The advent of diagnostic criteria for AE attempts to facilitate its prompt identification, but risks prematurely neglecting the potential scientific and clinical significance of isolated syndromes that do not satisfy these criteria. Here we propose using a syndrome-level taxonomy that has occasional, but not necessary, overlap with AE: synaptic and neuronal autoantibody-associated psychiatric syndromes or ‘SNAps’. This will prevent confusion with AE, and act heuristically to promote active investigation into this rare example of psychopathology defined on a molecular level. We suggest that this concept would have application in other autoantibody-associated syndromes including seizure, cognitive and movement disorders, in which similar issues arise. We review putative direct and indirect mechanisms and outline experimentally-testable hypotheses that would help to determine prospectively in whom autoantibody detection is relevant, and as important, in whom it is not. We summarise a pragmatic approach to autoantibody testing and management in severe mental illness in order to promptly diagnose AE and advocate a research-orientated experimental medicine paradigm for SNAps, where there is greater equipoise. We conclude that SNAps remains a nascent area of clinical neuroscience with great potential and in ongoing need of psychiatry-led basic and clinical research.